Festa e espaço urbano: meios de sonorização e bailes dançantes na Belém dos anos 1950 - COSTA, Antonio Maurício Dias da (Universidade Federal do Pará, 2017)
The article discusses the use of symbolic references from memoirs and periodicals attributed to the socio-spatial context of orchestral and sonoros balls in Belém, in the so-called ‘social clubs’ and ‘suburban clubs.’ The various forms of organizing dancing festivities in the city were connected to musical broadcasting on the radio in the 1950s, as well as being linked to the commercial sonoros or those specialized in dances. Different ways of using and accessing the means of communication by the urban inhabitants were looked after, especially focusing on the emphasis on social distinction in the local press. Symbols and values related to urban space emerge in newspapers and memoirs regarding the festive panorama of the city.